2020
DOI: 10.1200/go.20.00076
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Hospital-Based Pediatric Palliative Care: The Symptoms, Interventions, and Outcomes for Children With Cancer in Bangladesh

Abstract: PURPOSE The majority of pediatric cancer deaths occur in low- and middle-income countries (LMICs). Pediatric palliative care (PPC) focuses on relieving physical, psychosocial, and spiritual suffering throughout the continuum of cancer care and is considered integral to cancer care for children in all settings. There is limited evidence from LMICs about the characteristics, symptoms, and outcomes of children with cancer who receive PPC, which is needed to define the global need and guide the development of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A significant disparity in cure rate and mortality between high and low-income countries makes palliative care highly relevant in a paediatric oncology setting [3,4]. Empirical studies have shown that palliative care referral in a paediatric oncology setting improves the quality of life [5][6][7][8], pain and physical symptoms [6,[9][10][11][12][13][14][15][16][17], emotional support to children and their families [10,15,[18][19][20][21], communication between families and health care providers [11,15,16,[19][20][21][22][23][24][25][26], advance care planning and end-of-life care support [5, 12-16, 18, 20, 26-32].…”
Section: Introductionmentioning
confidence: 99%
“…A significant disparity in cure rate and mortality between high and low-income countries makes palliative care highly relevant in a paediatric oncology setting [3,4]. Empirical studies have shown that palliative care referral in a paediatric oncology setting improves the quality of life [5][6][7][8], pain and physical symptoms [6,[9][10][11][12][13][14][15][16][17], emotional support to children and their families [10,15,[18][19][20][21], communication between families and health care providers [11,15,16,[19][20][21][22][23][24][25][26], advance care planning and end-of-life care support [5, 12-16, 18, 20, 26-32].…”
Section: Introductionmentioning
confidence: 99%
“…Symptom management is a critical component of the physical domain of quality of life. Studies have shown symptom assessment [115,116] and symptom management benefit from paediatric palliative care referral [74,75,112,[115][116][117][118][119][120][121]. However, pain management benefit was better appreciated by children and families than the management of other symptoms [74,75,118,121].…”
Section: Outcomes Of Palliative Care Referral In Paediatric Oncologymentioning
confidence: 99%
“…Studies have shown symptom assessment [115,116] and symptom management benefit from paediatric palliative care referral [74,75,112,[115][116][117][118][119][120][121]. However, pain management benefit was better appreciated by children and families than the management of other symptoms [74,75,118,121]. Furthermore, some oncologists felt that palliative care could enable treatment completion by managing pain and symptoms whilst the child is receiving cancer-directed therapy.…”
Section: Outcomes Of Palliative Care Referral In Paediatric Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware of only 2 other studies describing the characteristics and symptoms of children receiving palliative care in resource limited settings. 13,14 These studies, in Bangladesh and Malawi, describe hospital-based palliative care programs which primarily include children with cancer and/or HIV/AIDS. 13,14 Our study is one of the first focussing on children in a community-based program.…”
Section: Children With Serious Health Conditionsmentioning
confidence: 99%